2012
DOI: 10.1007/s10433-012-0216-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in depression among older adults: are older women more vulnerable than men in social risk factors? The case of open care centers for older people in Greece

Abstract: This study examined depression, which, research has indicated, is the most common mental health problem affecting older people, especially women. Our objective was to estimate the prevalence of depression among older people in an urban Greek population and to investigate the covariates of depression symptoms prevalence by gender. The sample consisted of 360 individuals, 218 women and 142 men, aged 60 years or older, members of four open care centers for older people in Greece. A questionnaire for socio-demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
41
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 26 publications
9
41
0
1
Order By: Relevance
“…The present study results are in line with those in a systematic review study by Sajadi et al [29]. Review of prevalence of depression in the older adults in other countries shows different values, for instance, overall prevalence of depression in older adults of 30.3% in Greece [30], 16.8% in Netherlands [31], and 4.5% in Japan [32]. Review of studies on prevalence of depression in pregnant women with BDI showed prevalence of approximately 27.62%.…”
Section: Discussionsupporting
confidence: 91%
“…The present study results are in line with those in a systematic review study by Sajadi et al [29]. Review of prevalence of depression in the older adults in other countries shows different values, for instance, overall prevalence of depression in older adults of 30.3% in Greece [30], 16.8% in Netherlands [31], and 4.5% in Japan [32]. Review of studies on prevalence of depression in pregnant women with BDI showed prevalence of approximately 27.62%.…”
Section: Discussionsupporting
confidence: 91%
“…In a Korean study, Kim and Park (2012) found a significant gender difference in the proportion of older men and women with depression. Consistent with the findings of the present study Carayanni et al (2012) in an urban Greek population found that women had a higher prevalence of depression than men did.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we found that chronic symptom trajectory class membership was associated with a higher increase in hearing difficulties and multimorbidity, probably because of reward loss on a daily basis (e.g., difficulty in holding conversations), regardless of sex (Brewster et al, 2018;Rote et al, 2015). On the other hand, subclinical trajectory class membership was distinguished by a higher increase in visual difficulties over time probably due to a moderate loss of reward (i.e., visual impairment limits independence) and sensory disability (Freeman et al, 2016;Tolman et al, 2005).…”
Section: Discussionmentioning
confidence: 68%
“…In women, a higher amount of multimorbid conditions over time was linked with showing a rising symptom trajectory. Robust studies have shown a strong relationship between the onset of depression syndromes and multimorbidity, especially related to disease management and functional and social role losses (Carayanni et al, 2012;Chui et al, 2015;Marengoni et al, 2011).…”
Section: Discussionmentioning
confidence: 99%